Effects of feeding probiotic Lactobacillus spp. on growth performances, scours and Escherichia coli shedding in dairy calves - Amanullah, SM; Bateen, R; Huque, KS; Alam, MR; Alam, MS; Subarna, RN; Hossain, MM; Islam, KMR (Bangladesh Journal of Livestock Research, 2020)
A feeding trial was conducted on 21 crossbred (Local×Friesian, Local×Sahiwal, Sahiwal×Friesian) calves of around one week age for a period of 70 days with the objective of evaluating effects of probiotic on growth performances of calves. Calves were selected and distributed equally into three groups maintaining equal sex ratio in each group, namely the farm practice (FP), control and probiotic groups. The calves were fed on milk as 12% of their live weight up to 14 days and then 10% milk of their live weight up to 70 days of age and wheat bran was supplied to the calves from 50th day at the rate of 250g/calf. The calves of probiotic group werefedaprobiotic mixture containing lactic acid bacteria (LAB) at 0.5 g /d. The data of feed intake and growth for all groups were recorded up to 35 days and then up to 70 days for probiotic and control groups. The calves under probiotic group were achieved 82.8% and 74.5% higher gain (P<0.05) than that of FP and control group, respectively and feed conversion ratio was observed significantly (P<0.05) better in probiotic group (1.83) than that in FP (3.41) and the control group (3.50) up to 35 days of trial. However, no significant differences were found in average live weight gain and feed conversion ratio between probiotic and the control groups (1.99 vs 2.07, respectively) up to 70 days of the trial. Average counts of E. coli were lower in probiotic group than that in the control and FP. The incidence of diarrhoea in probiotic fed group was found 3 and 13 times lower compared to FP and the control group, respectively. Bangladesh J. of Livestock Res. 21-25: 89-102, 2018